Design and optimization of 22 nm gate length high-k/metal gate NMOS transistor - Afifah Maheran A.H.; Menon P.S.; Ahmad I.; Shaari S.; Elgomati H.A.; Salehuddin F. (Institute of Physics Publishing, 2023)
In this paper, we invented the optimization experiment design of a 22 nm gate length NMOS device which uses a combination of high-k material and metal as the gate which was numerically developed using an industrial-based simulator. The high-k material is Titanium dioxide (TiO2), while the metal gate is Tungsten Silicide (WSix). The design is optimized using the L9 Taguchi method to get the optimum parameter design. There are four process parameters and two noise parameters which were varied for analyzing the effect on the threshold voltage (Vth). The objective of this experiment is to minimize the variance of Vth where Taguchi's nominal-the-best signal-to-noise ratio (S/N Ratio) was used. The best settings of the process parameters were determined using Analysis of Mean (ANOM) and analysis of variance (ANOVA) to reduce the variability of Vth. The results show that the Vth values have least variance and the mean value can be adjusted to 0.306V 0.027 for the NMOS device which is in line with projections by the ITRS specifications.